Zeolite-Based Materials for the Catalytic Oxidation of VOCs: A Mini Review - Xue, Tianshan; Yang, Li (Frontiers in Chemistry, 2021)
Catalysts for VOCs combustion have been widely studied and zeolite-based materials and have been structured to meet the need of particle use in this field. This review summarized several new trends in zeolite-based catalysts for VOCs catalytic oxidation. Intensive effort has been devoted to the optimization of composition and structure of catalysts, abatement of CVOCs, design of zeolite-based monolithic catalysts and adsorbent/catalyst bi-functional material. The suggestions for further work here presented are put forward based on the collation of recently published papers.